Securing Web services practical usage of standards and specifications - Periorellis, Panos (Gale virtual reference library, 2008)
"This book collects a complete set of studies addressing the security and dependability challenges of Web services and the development of protocols to meet them. Encompassing a complete range of topics including specifications for message level security, transactions, and identity management, it enables libraries to provide researchers an authoritative guide to a most challenging technological topic"--Provided by publisher.